2010
DOI: 10.3109/10253891003786415
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of tissue plasminogen activator in stress responsivity during acute cocaine withdrawal in mice

Abstract: There is evidence that increased release of corticotropin-releasing factor (CRF) in the central nucleus of the amygdala (CeA) contributes to stress responsivity during cocaine withdrawal (WD). Recent studies suggest that tissue plasminogen activator (tPA) in the CeA is a downstream effector protein for CRF after acute “binge” cocaine administration. The purpose of this study was to determine if tPA modulates cocaine WD-induced stress responsivity. Wild-type (WT) and tPA-deficient (tPA −/−) mice were subjected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…On the basis of this evidence, we hypothesize that increased basal levels of dynorphin in the nucleus accumbens core may lead to altered dopaminergic signaling after drug exposure. Indeed, in our studies, cocaine-induced conditioned place preference and locomotor sensitization, as well as cocaine withdrawal-induced stress responses, are attenuated in tPA knockout mice (Maiya et al, 2009;Zhou et al, 2010b). Our work also indicates a potential involvement of glial systems in cocaine rewarding and stress responsivity.…”
Section: Section IV Dynorphin and Kappa Opioid Receptor Stress Resposupporting
confidence: 53%
“…On the basis of this evidence, we hypothesize that increased basal levels of dynorphin in the nucleus accumbens core may lead to altered dopaminergic signaling after drug exposure. Indeed, in our studies, cocaine-induced conditioned place preference and locomotor sensitization, as well as cocaine withdrawal-induced stress responses, are attenuated in tPA knockout mice (Maiya et al, 2009;Zhou et al, 2010b). Our work also indicates a potential involvement of glial systems in cocaine rewarding and stress responsivity.…”
Section: Section IV Dynorphin and Kappa Opioid Receptor Stress Resposupporting
confidence: 53%
“…Loss-of-function mutations in the GRIN1 , GRIN2A, and GRIN2B genes were found in patients suffering from a variety of neurodevelopmental disorders ranging from childhood encephalopathy to intellectual disability or autism [ 264 , 265 ]. tPA is expressed at a high rate in various brain structures, including the amygdala, hippocampus, and cerebellum [ 266 , 267 ]. An interesting study published in 2016 showed an elevated level of tPA and some adhesion molecules in the serum of children with ASD [ 268 ].…”
Section: Cns Diseases and Nmdar Dysfunctionsmentioning
confidence: 99%
“…Additionally, amygdaloid tPA has been implicated in regulating stress responses during acute cocaine withdrawal (Zhou, Maiya, Norris, Kreek, & Strickland, 2010). These examples illustrate the importance that glial and neuronal compartments be considered as not discrete entities, but rather as highly inter-connected structures which collaboratively influence neuronal plasticity (Todd, Serrano, Lacaille, & Robitaille, 2006).…”
Section: Introductionmentioning
confidence: 99%